Reformers, Teachers, Writers : Curricular and Pedagogical Inquiries - Lerner, Neal (Book collections on Project MUSE., 2019)
"Exploring the distinction between curriculum and pedagogy focused on curriculum and its importance in many contexts in which writing plays a role. Using a mixed-methods approach of quantitative, qualitative, textual, historical, narrative, and theoretical methods that reflects the importance and effects of curriculum in different settings"--Provided by publisher